Effects of a Reinforcement Schedule Controlling Energy of Pigeons’ Pecking Response - Kono, Masanori (The Psychological record, 2017)
Operant behavior involves many physical dimensions, including time, force, location, and distance. Energy is an important dimension in foraging behavior or motor response. Kono ( Learning & Behavior, 41 , 425–432, 2013 ) developed a schedule in which the controlling variable was the energy of responses, calculated by dividing the squared value of the distance between two consecutive responses by the squared value of the interresponse time, or the elapsed time between the two responses. This energy schedule demonstrated the possibility of differential reinforcement of the energy of responses, but the effect was relatively weak. Kono ( Learning & Behavior, 41 , 425–432, 2013 ) proposed that this weak effect could have been caused by two features of the adjusting procedure: the use of two or more schedules and variation in the reinforced energy of responses across trials depending on the subjects’ previous choice. The present study employed a single energy schedule whose requirement was fixed throughout the session. The results showed that the energy of responses increased as the requirement of the energy schedule increased. In addition, the degree of increase was greater for distance of responses than for time of responses. These results suggest that the energy schedule is a suitable method for controlling the energy of behavior, and the distance of responses has a greater effect than time.